DNA Metabarcoding for Quality Control of Basil, Oregano, and Paprika - Raclariu-Manolică, Ancuţa Cristina; Anmarkrud, Jarl Andreas; Kierczak, Marcin; Rafati, Nima; Thorbek, Birgitte Lisbeth Graae; Schrøder-Nielsen, Audun; de Boer, Hugo J. (Frontiers in Plant Science, 2021)
Herbs and spices are some of the vulnerable products in terms of fraud and adulteration in the food sector. Although standard analytical methods are accurate for quality control of specific lead or marker compounds, they cannot accurately assess the entire species composition of many marketed products. Complementary analytical approaches are thus often used for comprehensive screening of herbs and spices. In this study we evaluate DNA metabarcoding for the identification and authentication of 62 products, containing basil, oregano, and paprika collected from different retailers and importers in Norway. Our results show varying degrees of discrepancy between the constituent species and those listed on the product labels, despite high product authenticity. We suggest the false positives result from the sensitivity of DNA metabarcoding and filtering thresholds should be integrated into protocols to reduce false positives. Our results highlight how integrating DNA metabarcoding into the toolbox of analytical methods for quality control of analytical methods for fresh and/or processed plant-based food can improve product quality.